AGIA Tag System for Ultrastructural Protein Localization Analysis in Blood-Stage Plasmodium falciparum - Morita, Masayuki; Kanoi, Bernard N.; Shinzawa, Naoaki; Kubota, Rie; Takeda, Hiroyuki; Sawasaki, Tatsuya; Tsuboi, Takafumi; Takashima, Eizo (Frontiers in Cellular and Infection Microbiology, 2021)
Precise subcellular localization of proteins is the key to elucidating the physiological role of these molecules in malaria parasite development, understanding of pathogenesis, and protective immunity. In Plasmodium falciparum, however, detection of proteins in the blood-stage parasites is greatly hampered by the lack of versatile protein tags which can intrinsically label such molecules. Thus, in this study, to develop a novel system that can be used to evaluate subcellular localization of known and novel proteins, we assessed the application of AGIA tag, consisting of 9 amino acids (EEAAGIARP), in P. falciparum blood-stage parasites. Specifically, AGIA-tagged ring-infected erythrocyte surface antigen (RESA-AGIA) was episomally expressed in P. falciparum 3D7 strain. The RESA-AGIA protein was detected by Western blotting and immunofluorescence assay (IFA) using recombinant rabbit anti-AGIA tag monoclonal antibody (mAb) with a high signal/noise ratio. Similarly, AGIA-tagged multidrug resistance protein 1 (MDR1-AGIA), as an example of polyptic transmembrane protein, was endogenously expressed and detected by Western blotting and IFA with anti-AGIA tag mAb. Immunoelectron microscopy of the RESA-AGIA transfected merozoites revealed that mouse anti-RESA and the rabbit anti-AGIA mAb signals could definitively co-localize to the dense granules. Put together, this study demonstrates AGIA tag/anti-AGIA rabbit mAb system as a potentially useful tool for elucidating the subcellular localization of new and understudied proteins in blood-stage malaria parasites at the nanometer-level resolution.